State and prospects of development of financial decentralization in Ukraine - Byvshev, R.; Voloshyna, О. (Економічний вісник Донбасу, 2018)
The article analyzes the current problems of the formation of local budgets and systematizes proposals on the prospects of financial decentralization in the context of the need for reforming the power system in Ukraine. The priority directions of the management of public finances are defined: substantiated formation, transparent distribution and redistribution and effective use, which will promote effective management of budgetary funds in the country. It is proved that the improvement of the legal and institutional framework of the system of intergovernmental financing will contribute to the implementation of effective budget reforms. У статті проведено аналіз сучасних проблем формування місцевих бюджетів та систематизації пропозицій щодо перспектив фінансової децентралізації в контексті необхідності реформування системи влади в Україні. Визначено пріоритетні напрями управління державними фінансами: обґрунтоване формування, прозорий розподіл і перерозподіл та ефективне використання, що буде сприяти ефективному управлінню бюджетними коштами в країні. Доведено, що вдосконалення правової та інституційної бази системи міжбюджетного фінансування буде сприяти проведенню ефективних бюджетних реформ. В статье проведен анализ современных проблем формирования местных бюджетов и систематизации предложений относительно перспектив финансовой децентрализации в контексте необходимости реформирования системы власти в Украине. Определены приоритетные направления управления государственными финансами: обосновано формирование, прозрачное распределение и перераспределение, а также эффективное использование, которое будет оказывать содействие эффективному управлению бюджетными средствами в стране. Доказано, что усовершенствование правовой и институционной базы системы межбюджетного финансирования будет оказывать содействие проведению эффективных бюджетных реформ.